Marriage Law Perspective Against Underage Marriage - Prasetyo , Budi; Sanjaya, Edy; Hastuti, Indira (International Journal of Educational Research & Social Sciences, 2022)
Underage marriages have been happening in Indonesia for a long time, especially in rural communities that are categorized as not yet advanced in their level of education, economy, or because of the local community's traditions. From the perspective of the Marriage Law, this is contrary to the provisions of Article 7 paragraph (1) of Law Number 16 of 2019 and is contrary to the purpose of marriage is to form an eternal family based on God Almighty. Early marriage in adolescents impacts the physical aspect and psychological impact on the perpetrators. The research method is empirical juridical research. The research specification in this study is descriptive-analytical. The study results show that the existence of underage marriages, this indicates that Law Number 1 of 1974 concerning Marriage and Government Regulation Number 9 of 1975 concerning Implementing Regulations of Law Number 1 of 1974, is less effective. Given the existence of underage marriages, many divorces occur because the marriages are carried out by children who are still underage, so they have not been able to carry out the purpose of marriage fully.